DEVELOPING POCKET BOOK OF ISLAMIC RELIGION (POKEMON) LEARNING MEDIA TO ENHANCE THE STUDENTS’ LEARNING MOTIVATION - Siti Sofiyatun; Zumrotul Fauziah; Moh Miftahul Choiri (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This research aimed to develop learning media in the form of a Pocketbook of Islamic Religion (POKEMON) using the Flipbook application. This research focused on the feasibility and the implementation of the learning media. The method of this research was Research and Development (R & D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This model had 5 stages: First was analysis, the stage of analyzing the situation and condition in which the media is needed for the learning process. The second stage was design, which is the stage of designing the learning media being developed. The third stage was developing learning media using the flipbook application. After the media has been developed, the next stage is implementation, namely the implementation stage for students to find out the feasibility and practicality of the media. The last stage was the evaluation, which aimed to improve the product after it has been tested and implemented. The result of the study showed that the media has high feasibility with a percentage of media expert assessments of 86.7%, material experts 91.5%, and 94.2%. Furthermore, the students perceived that the POKEMON media helps and motivates them in the learning process. The media had a positive impact on students such as making it easy to understand the material, so that students become enthusiastic in learning and reading, and trains students to think critically. Thus, this media had very valid and practical to use as a media in the learning process.